Posttraumatic Stress Symptoms and Binge Eating With Mental Escape Features. Issue 8 (17th November 2018) - Witte, Tricia H.; Jordan, Hallie R.; Michael, Megan L.
Abstract: The current study examines the association between posttraumatic stress symptoms and the experience of mental escape during binge eating. Participants were 898 undergraduate students at a large university in the southeastern United States. Results found that posttraumatic stress symptoms predicted (a) binge eating frequency and (b) mental escape during binge eating, even after controlling for emotion regulation deficits and other well-established predictors of binge eating (e.g., body weight and shape concerns). The results of this study are consistent with theories that conceptualize binge eating as an attempt to escape negative affect regarding past trauma. Results have implications for trauma-focused psychotherapy.